Interprofessional collaboration competency: perspectives of doctors and other healthcare professionals - Wiwik Kusumawati; Elsye Maria Rosa; Ekorini Listiowati; Prita Anggraini Kartika Sari; Arif Riyanto; Rozzali Taufiqurrahman; Muhammad Roihan Naufal; Suryani Suryani (Universitas Aisyiyah Yogyakarta, 2026)
Healthcare professionals are responsible for providing quality services, but their role is still not optimal, which can lead to medical errors. Therefore, collaborative practice is important for being able to provide effective and efficient services. This study aims to assess and compare interprofessional collaboration competencies among different healthcare professionals at PKU Muhammadiyah Gamping Hospital. This is quantitative research used an analytical observational design with a cross-sectional approach. The Instrument Interprofessional Collaborative Competency Attainment Survey (ICCAS) was distributed to 113 respondents consisting of 26 doctors, 79 nurses, and 8 pharmacists who were selected randomly using cluster sampling. Data were analyzed using multiple linear regression tests and chi-square tests. The results of the research show that the average percentage of interprofessional collaboration competency for healthcare professionals at PKU Muhammadiyah Gamping Hospital is 81.5%, with details of doctors at 77.5%, nurses at 83.0%, and pharmacists at 81.0%. The interprofessional collaboration competency domain with the highest percentage is collaboration, with 83.0%, and the lowest is roles and responsibilities, with 80.0%. Then the results of the Chi-Square statistical test obtained a significance value of 0.002 (p < 0.05). This shows that there are factors that challenge the realization of interprofessional collaboration, namely the perception of an imbalance in hierarchy and power between professions, as well as a lack of understanding of each other's skills and knowledge. Hospitals should implement in-house training and standard operating procedures for interprofessional collaboration, while educational institutions must evaluate and strengthen interprofessional education programs to improve patient safety and care quality.